Rainbow Jews : Jewish and gay identity in the performing arts - Friedman, Jonathan C., 1966- (Lexington Books, 2007)
"Rainbow Jews deals with the intersection of gay and jewish identity in American and Israeli film and theater from the 1960s to the present. Its main area of interest is the extent to which Jewish creative voices in the performing arts have constructed multidimensional images of, and a welcoming public space for, the gay, lesbian, and transgendered community as a whole. Through a close reading of numerous American and Israeli plays and films, Jonathan Friedman evaluates some of the key conventions and tropes that have been employed to construct, critique, and reflect the social reality of the connection between Jewishness and gay identity in the United States and Israel."--Jacket